Processing influence on dielectric, mechanical, and electrical properties of reduced graphene oxide–TPU nanocomposites. Issue 12 (30th October 2018) - Gómez, Julio; Recio, Imanol; Navas, Ana; Villaro, Elvira; Galindo, Begoña; Ortega‐Murguialday, Amaya
ABSTRACT: Two different reduced graphene oxides (rGOs) with similar concentration of oxygen and defects and differences in exfoliation were prepared to produce the rGO/thermoplastic polyurethane nanocomposites by solution blending (SB) and melt compounding (MC). Morphology, electrical, and dielectric properties were studied. Large agglomerates have been observed for the composites produced by SB and discrete and low agglomerated rGO particles in the case on the composites produced by MC. These morphological differences justify the observations in hardness, electrical conductivity, and even in the dielectric properties. The composites do not follow Jonscher's universal power law (UPL) and a linear trend between UPL factors (Log A vs n ) has been observed for composites produced by SB, however, no trend is observed in the composites produced by MC, being the first time observed. Differences in the tunneling effect and breakage of H‐bonds within the polymer can be suggested from the dielectric relaxation characterization. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47220. Abstract :